(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The article presents the effect of different sowing dates and norms of camelina sativa (Camelina sativa L) varieties on the oil content of seeds. According to this, it was found that when camelina sativa plants were planted at different dates and norms, the oil content of seeds decreased with increasing sowing norm.